Teaching English to Young Learners and Factors to Consider in DesigningThe Materials - - Sukarno (Universitas Negeri Yogyakarta, 2008)
Teaching English to young learners at elementary school is different from that to adults. The English teachers to young learners in elementary school, therefore, need to comprehend and to apply the theories of language teaching-learning to young learners and language classroom management. Besides, the English teachers are not only required to be able to teach well but also to be able to design materials so that they can apply approaches, methods, and techniques of teaching-learning English appropriately.This article discusses teaching English to young learners, the theories of teaching English to young learners at elementary school, English classroom management at elementary school, and what to consider in designing teaching-learning materials.To reach the goal of the teaching and learning of English at elementary school, the English teachers at elementary school should know and apply the theories of teaching English to young learners. Besides, they should also know what to consider in designing teaching-learning materials in order that the materials given to the students are appropriate for the students development in relation to languages.